Rat retinal function attenuation with IOP elevation is impacted by both blood pressure and intracranial pressure - Ganearachchi, Sera N.; van Koeverden, Anna K.; Nguyen, Christine T. O.; He, Zheng; Wong, Vickie H. Y.; Bui, Bang V.; Zhao, Da (Frontiers in Physiology, 2025)
IntroductionTo consider how blood pressure and intracranial pressure modify the way that retinal function responds to intraocular pressure elevation in rats.MethodsSix groups of adult Long–Evans rats (n = 7–11 eyes/group, total animals 25) were anesthetized and underwent acute pressure modification. Blood pressure (BP) was measured via a femoral artery cannula and elevated by angiotensin II infusion into the femoral vein. Intracranial pressure (ICP) was set to 0 mmHg, 5 mmHg, or 25 mmHg in three separate groups of rats via a cannula in the lateral ventricle. At each ICP (−5 mmHg, 5 mmHg, or 25 mmHg) and BP setting (normal or high), intraocular pressure (IOP) was increased from 10 mmHg to 90 mmHg in 10 mmHg steps. At each IOP level, ganglion retinal function was assessed using the electroretinogram.ResultsCompared with normal blood pressure groups, animals with high blood pressure had significantly smaller baseline ganglion cell-mediated scotopic threshold responses (STR). Animals with high ICP had larger scotopic threshold response (STR) amplitudes than the normal and low ICP groups. Both high BP and high ICP rendered retinal function less susceptible to IOP elevation; however, the effect was greater for high BP.ConclusionRetinal function is critically dependent on ocular perfusion pressure; excessive low or high perfusion attenuates function. The ocular perfusion pressure (BP–IOP) relationship largely accounts for the effect of IOP and BP modulation on retinal function but could not account for differences in ganglion cell function between ICP levels.